2013
DOI: 10.1080/14635240.2013.830452
|View full text |Cite
|
Sign up to set email alerts
|

An independent evaluation of a home safety equipment scheme in a high-risk community: views and safety practices of families

Abstract: Unintentional injury is a major public health issue across the world. The home is the most common location for unintentional injuries for young children, with children living in socio-economically deprived circumstances most at risk of injury. The provision of home safety education, with or without the provision of free or low-cost safety equipment, has been shown to improve home safety practices undertaken by parents. An evaluation was undertaken of a home safety equipment running in northeast England. A rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A previous evaluation of the SAH scheme showed that it reached families at higher risk of child injuries, 16 and parents reported high levels of satisfaction, 17 equipment use and other safety behaviours. 16 However, this evaluation did not include assessment of the effect on child injuries.…”
Section: Introductionmentioning
confidence: 91%
“…A previous evaluation of the SAH scheme showed that it reached families at higher risk of child injuries, 16 and parents reported high levels of satisfaction, 17 equipment use and other safety behaviours. 16 However, this evaluation did not include assessment of the effect on child injuries.…”
Section: Introductionmentioning
confidence: 91%
“…The SAH scheme provided home safety assessments, advice and supplied and fitted a range of home safety equipment to disadvantaged families with children aged under five who were receiving means-tested state financial support 18. The SAH scheme has previously been shown to significantly reduce hospital admission rates,5 reaching families with children at increased injury risk19 with high levels of parent satisfaction,20 equipment use and other safety behaviours 19. However, no economic evaluation of the SAH scheme has been conducted to date.…”
Section: Introductionmentioning
confidence: 99%